Genetic diversity, antimicrobial resistance, and virulence genes of thermophilic Campylobacter isolated from broiler production chain - Ramires, Tassiana (Braz J Microbiol, 2020)
The aim of this study was to investigate the prevalence of thermophilic Campylobacter in the broiler production chain of southern Brazil, by evaluating broiler farms and slaughter line samples, and to determine the genetic diversity, antimicrobial resistance, and virulence genes of the isolates. Of the 140 samples investigated in this study, 75 (53.6%) were positive for thermophilic Campylobacter, and all isolates were identified by phenotypic and molecular tests as C. jejuni. The resistance to nalidixic acid was the most common (74%), followed by resistance to enrofloxacin (67.3%) and ciprofloxacin (37.1%). However, there was no resistance to the macrolides tested which are recommended for the treatment of human campylobacteriosis. The PFGE showed that the isolates were grouped in eight macrorestriction patterns (P1 to P8). A representative isolate of each macrorestriction pattern was investigated for the presence of virulence genes and all isolates carried the cadF, ciaB, cdtA, cdtB, cdtC, and flaA genes. The dnaJ gene was detected in 87.5% (7/8) of the isolates. The flhA and racR genes were detected in 75% (6/8), while the pldA gene was present in 62.5% (5/8) and the wlaN gene in 25% (2/8). The presence of C. jejuni in broiler farms and in the slaughterhouse is a hazard to consumer given that this pathogen can be maintained throughout the broiler production chain and contaminates the final product. Moreover, the presence of the major virulence genes in the isolates demonstrates that they have the ability to develop campylobacteriosis in humans.